Is the EU money market fund regulation fit for purpose? Lessons from the COVID-19 turmoil - Laura-Dona Capotæa; Michael Grill; Luis Molestina Vivar; Niklas Schmitz; Christian Weistroffer (European Central Bank (ECB), 2022)
The market turmoil in March 2020 highlighted key vulnerabilities in the EU money market fund (MMF) sector. This paper assesses the effectiveness of the EU's regulatory framework from a financial stability perspective, based on a panel analysis of EU MMFs at a daily frequency. First, we find that investment in private debt assets exposes MMFs to liquidity risk. Second, we find that low volatility net asset value (LVNAV) funds, which invest in non-public debt assets while offering a stable NAV, face higher redemptions than other fund types. The risk of breaching the regulatory NAV limit may have incentivised outflows among some LVNAV investors in March 2020. Third, MMFs with lower levels of liquidity buffers use their buffers less than other funds, suggesting low levels of buffer usability in stress periods. Our findings suggest fragility in the EU MMF sector and call for a strengthened regulatory framework of private debt MMFs.
Keywords: G11; G15; G23; G28; 330; money market funds; financial fragility; COVID-19; regulation